The future of agriculture and agricultural policy: perceptions of non-farmers and farmers - Tienhaara, Annika; Niemi, Jyrki; Vainio, Annukka; Pouta, Eija (Scientific Agricultural Society of Finland, 2024)
We examined the views of Finnish non-farmers and farmers on the desirable future developments of agriculture and agricultural policy using principal component and cluster analysis by focusing on three key themes: the structure of agricultural production, agri-environmental issues, and the funding of agriculture. There is strong public support for maintaining the viability of domestic agriculture through government intervention, but views differ on allocation of agricultural support and how agricultural production should be developed. A significant number of respondents supported the idea that climate and other environmental issues should be better considered in agricultural policy. However, about half of the respondents accepted environmental damage caused by agriculture and one-fifth perceived the importance of agriculture in a society as declining. These views, not prominent in the public debate, emphasize the importance of regular investigation of citizen opinions for including all the relevant stands in policy discussion to design legitimate policy measures.
Keywords: citizen; clusters; perceptions; structure of agriculture; agri-environmental issues; funding of agriculture